1999
DOI: 10.1111/j.1348-0421.1999.tb02367.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Conditions of and Emetic Toxin Production by Bacillus cereus in a Defined Medium with Amino Acids

Abstract: The growth and emetic toxin (cereulide) production of Bacillus cereus strains in defined culture media were studied. We found that a fully synthetic medium (CADM) allowed the production of emetic toxin and the addition of glucose enhanced it. By subtracting each amino acid from CADM, we found that only three amino acids, valine, leucine and threonine, were essential for growth and toxin production by B. cereus. The addition of high levels (50 mm) of leucine, isoleucine and glutamic acid decreased the toxin pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Products classified as being insensitive were dairy based, displayed a low pH value (e.g., cream cheese and unsweetened quark), had a high fat content like chocolate and nut spread, and/or were characterized by low water availability or high osmolarity (e.g., dried fruits and 10% herbal salt solution). Earlier studies showed that growth of B. cereus was suppressed in foods with pH values below 5.0 [3436], which is in line with our low-risk classification of matrices that had pH values around 4.3 to 4.8, such as the whey drinks. The combination of neutral pH values and medium a w -values with high amounts of fat and cocoa was found to be indicative of the group of products being at medium risk of toxin synthesis (Table 2 and Figure S2).…”
Section: Resultssupporting
confidence: 89%
“…Products classified as being insensitive were dairy based, displayed a low pH value (e.g., cream cheese and unsweetened quark), had a high fat content like chocolate and nut spread, and/or were characterized by low water availability or high osmolarity (e.g., dried fruits and 10% herbal salt solution). Earlier studies showed that growth of B. cereus was suppressed in foods with pH values below 5.0 [3436], which is in line with our low-risk classification of matrices that had pH values around 4.3 to 4.8, such as the whey drinks. The combination of neutral pH values and medium a w -values with high amounts of fat and cocoa was found to be indicative of the group of products being at medium risk of toxin synthesis (Table 2 and Figure S2).…”
Section: Resultssupporting
confidence: 89%
“…No cereulide production was found in peptone broth [57]. The presence of glucose tends to support cereulide production while excessive amounts of leucine, isoleucine, and glutamic acid significantly repress cereulide formation [58]. In food systems, the highest rates have been observed in rice and pasta while toxin production in bread and cakes was low [59,60].…”
Section: Emetic Toxin Expressionmentioning
confidence: 98%
“…Differences in levels of cereulide production between strains have also been observed (Häggblom et al , 2002; Rajkovic et al , 2006) and are possibly due to differences in regulation, because the ces genes themselves show only a low level of heterogeneity (Ehling‐Schulz et al , 2005b). Furthermore, environmental factors such as oxygen, pH, temperature and the presence of specific amino acids have been described to influence the production of cereulide (Agata et al , 1999; Finlay et al , 2000; Ehling‐Schulz et al , 2004b; Jääskeläinen et al , 2004), and it has been shown that stationary incubation of food supports a higher level of cereulide production compared with aerated incubation (Rajkovic et al , 2006; Shaheen et al , 2006). However, the mechanisms regulating cereulide synthesis are still largely unknown.…”
Section: Cereulide the Emetic Toxinmentioning
confidence: 99%